A Comparison of Urge Intensity and the Probability of Tic Completion During Tic Freely and Tic Suppression Conditions. (March 2014) - Specht, Matt W.; Nicotra, Cassandra M.; Kelly, Laura M.; Woods, Douglas W.; Ricketts, Emily J.; Perry-Parrish, Carisa; Reynolds, Elizabeth; Hankinson, Jessica; Grados, Marco A.; Ostrander, Rick S.; Walkup, John T.
Tic-suppression-based treatments (TSBTs) represent a safe and effective treatment option for Chronic Tic Disorders (CTDs). Prior research has demonstrated that treatment naive youths with CTDs have the capacity to safely and effectively suppress tics for prolonged periods. It remains unclear how tic suppression is achieved. The current study principally examines how effective suppression is achieved and preliminary correlates of the ability to suppress tics. Twelve youths, ages 10 to 17 years, with moderate-to-marked CTDs participated in an alternating sequence of tic freely and reinforced tic suppression conditions during which urge intensity and tic frequency were frequently assessed. Probability of tics occurring was half as likely following high-intensity urges during tic suppression (31%) in contrast to low-intensity urges during tic freely conditions (60%). Age was not associated with ability to suppress. Intelligence indices were associated with or trended toward greater ability to suppress tics. Attention difficulties were not associated with ability to suppress but were associated with tic severity. In contrast to our "selective suppression" hypothesis, we found participants equally capable of suppressing their tics regardless of urge intensity during reinforced tic suppression. Tic suppression was achieved with an "across-the-board" effort to resist urges. Preliminary data suggest that ability to suppress may be associated with general cognitive variables rather than age, tic severity, urge severity, and attention. Treatment naive youths appear to possess a capacity for robust tic suppression. TSBTs may bolster these capacities and/or enable their broader implementation, resulting in symptom improvement.